Bulging amniotic membranes at 26 weeks with hindwater leakage. Amnioreduction, rescue double cervical cerclage, subsequent frank membrane rupture and severe oligohydramnios - Ramsewak, Samuel; Timothy, Marlon; R. Gidla, Sanju; Brathwaite, Earl; Chinnia, Javed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
A 39-year-old, gravida 3 para 0+2 presented at 26+4 weeks gestation with a clear vaginal discharge which upon speculum examination revealed prominent bulging amniotic membranes and a pool of clear amniotic fluid in the vagina. Abdominal ultrasound showed a single viable fetus in longitudinal lie, cephalic presentation and fetal heart rate (FHR) 150 beats per minute, regular. Estimated fetal weight 863g. The past history included 2 previous missed miscarriages. A diagnosis of pre-term premature hind water rupture of membranes was made. Intravenous antibiotics, magnesium sulphate, intramuscular progesterone and antenatal steroids were administered and emergency (double) cervical cerclage was performed after amnioreduction. The next day, the patient showed features of frank rupture of membranes and severe oligohydramnios on ultrasound. Six weeks after cerclage (32+4) considering the persistent amniotic fluid leakage with severe oligohydramnios, planned Caesarean section delivery was performed and a male fetus, weighing 1790 grams was delivered with APGAR scores of 7 and 8 at 1 and 5 minutes respectively. NICU care included invasive volume targeted ventilation, double dose surfactant administration and management of neonatal sepsis with β-haemolytic streptococci. Echocardiographic assessment was normal and feeds were initiated after 3 days of oral immune therapy using colostrum. After 14 days of NICU stay, the neonate was discharged.